The Effect Of Electronic Word Of Mouth (E-WOM) On Online Purchase Intention: A Case Study Of Consumer Of Barenbliss - Nurfadillah, Aisya; Widarmanti, Tri (eProceedings of Management, 2024)
The cosmetics industry is one of the leading sectors in Indonesia. Industrial development and progress are increasinglyrapid. The rapid progress of the industrial sector has given rise to increasingly tight levels of business competition.The cosmetics sector has greatly benefited from the rapid development of e-commerce. Sociolla is the largest beautye-commerce platform in Indonesia used by Barenbliss cosmetic products. The use of e-commerce is closely related toelectronic word of mouth and online purchasing activities. The purpose of this research is to determine the influenceof Electronic Word of Mouth on Online Purchases on Purchase Interest in Barenbliss products. The research wasconducted using quantitative methods, data was collected from 110 respondents using a Google form questionnaire.The data was then processed using SPSS version 29. The research results show that Information Quality, InformationQuantity, Information Credibility, Information Usefulness, and Information Adoption influence Purchase Intentions.Beauty products should be able to provide quality information, in this case information that is understandable, clearand in accordance with the facts and relevant to consumer needs, the credibility of the information, and informationthat can help consumers make purchasing decisions will greatly influence purchase intentions. Keyword-electronic word-of-mouth, online purchase intention, information quality, information quantity, informationusefulness, information adoption, Barenbliss